European consensus-based recommendations for the diagnosis and treatment of rare paediatric vasculitides – the SHARE initiative. (7th December 2018) - de Graeff, Nienke; Groot, Noortje; Brogan, Paul; Ozen, Seza; Avcin, Tadej; Bader-Meunier, Brigitte; Dolezalova, Pavla; Feldman, Brian M; Kone-Paut, Isabelle; Lahdenne, Pekka; Marks, Stephen D; McCann, Liza; et al.
Abstract: Objectives: The European initiative Single Hub and Access point for paediatric Rheumatology in Europe (SHARE) aimed to optimize care for children with rheumatic diseases. Systemic vasculitides are very rare in children. Consequently, despite recent advances, paediatric-specific information is sparse. The lack of evidence-based recommendations is an important, unmet need. This study aimed to provide recommendations for diagnosing and treating children with rare forms of childhood systemic vasculitis. Methods: Recommendations were developed by a consensus process in accordance with the European League Against Rheumatism standard operating procedures. A systematic literature review informed the recommendations, which were devised and evaluated by a panel of experts via an online survey, and two consensus meetings using nominal group technique. Recommendations were accepted when ⩾ 80% of experts agreed. Results: Ninety-three relevant articles were found, and 78 recommendations were accepted in the two consensus meetings. General, cross-cutting recommendations and disease-specific statements regarding the diagnosis and treatment of childhood-onset PAN, granulomatosis with polyangiitis, microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis, and Takayasu arteritis are provided. Conclusion: These Single Hub and Access point for paediatric Rheumatology in Europe recommendations were formulated through an evidence-based consensus process to support uniform, high-quality standard of care for children with rare forms of paediatric systemic vasculitis.